Accounting for the emergy value of life cycle inventory systems: Insights from recent methodological advances - Arbault, Damien; Rugani, Benedetto; Marvuglia, Antonino; Tiruta-Barna, Ligia; Benetto, and Enrico (Journal of Environmental Accounting and Management, 2026)
Emergy, due to its unique ability to translate into a single metric the memory of the geobiosphere exergy (environmental work) supporting any (technological or natural) system, has the potential to offer a new perspective of environmental assessment to support decision-making. Previous work by a number of researchers has pointed out the expected advantages of taking a hybrid approach combining Emergy Evaluation (EME) and Life Cycle Assessment (LCA). In particular, emergy calculation using Life Cycle Inventory (LCI) databases and LCA matrix-based formulation is claimed to have the potential to increase the reliability of emergy-based evaluations and thereby the applicability of the emergy concept in environmental decision-making. The paper points out the main obstacles to overcome in order to reach this consistent integration, highlighting the progresses made so far in this direction, until the most recent practical and operational advancements.